Experimental on-farm trials data of faba bean and wheat intercropping field validation in Lebanon and Morocco - Maalouf, Fouad; Abou-Khater, Lynn; Agrawal, Shiv Kumar; Hejjaoui, Kamal; Morda, Walaa; Hayek, Perla; Chalak, Lamis; Jeitani, Asma; Bartolini, Pietro (Elsevier, 2022)
This data paper describes the content of four datasets col- lected by the International Center for Agricultural Research in the Dry Areas (ICARDA) as a partner in the project “Designing InnoVative plant teams for Ecosystem Resilience and agricultural Sustainability (DIVERSify)”with the objec- tive of assessing the feasibility of faba bean-wheat mix- ture in Mediterranean environments under diverse rainfed conditions. Data was collected during the trials conducted in Kfardan-Lebanon during 2017/2018 where 40 faba bean varieties were evaluated as sole and as mixture with 2 wheat cultivars ‘Margherita’ and ‘Miki’ and during 2018/2019 where 40 faba bean varieties and one durum wheat cultivar ‘Margherita’ were evaluated under low rainfall environments. Trials were also conducted in Tal Amara-Lebanon during 2019/2020 where 20 faba bean lines and one durum wheat cultivar ‘Margherita’ were evaluated under high rainfall en- vironments and in Marchouch-Morocco during 2019/2020 where 7 faba bean lines with 3 cultivars and one durum wheat cultivar ‘Margherita’ were evaluated under extremely low rainfall environments. A detailed list of the different bi- ological traits collected for wheat and faba bean is found in the specification table in this article. The Kfardan 2018/ 2019, Tal Amara and Marchouch data is related to the conference paper “Performance of faba bean-wheat mixture under di- verse Mediterranean environments”.